Selective C−N Borylation of Alkyl Amines Promoted by Lewis Base. (17th October 2018) - Hu, Jiefeng; Wang, Guoqiang; Li, Shuhua; Shi, Zhuangzhi
Abstract: An efficient method for the metal‐free deaminative borylation of alkylamines, using bis(catecholato)diboron as the boron source, to directly synthesize various alkyl potassium trifluoroborate salts is introduced. The key to this high reactivity is the utilization of pyridinium salt activated alkylamines, with a catalytic amount of a bipyridine‐type Lewis base as a promoter. This transformation shows good functional‐group compatibility (e.g., it is unimpeded by the presence of a ketone, indole, internal alkene, or unactivated alkyl chloride) and can serve as a powerful synthetic tool for borylation of amine groups in complex compounds. Mechanistic experiments and computations suggest a mechanism in which the Lewis base activated B2 cat2 unit intercepts an alkyl radical generated by single‐electron transfer (SET) from a boron‐based reductant.